PEMANFAATAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI KELAS X MERDEKA 1 SMA NEGERI 3 JENEPONTO: The Use of the Discovery Learning Model in Teaching Expository Writing to Grade X Merdeka 1 Students at State Senior High School 3 Jeneponto - Aulia, Irma Anugrah; Usman; Asia. M (Journal of Applied Linguistics and Literature, 2025)
This research aims to find out the problems in learning writing that occur in Senior High School, especially in writing exposition texts. The purpose of this study is to determine the implementation and results of utilising the discovery learning model. The model used in this research is descriptive. The research sample is X Merdeka 1 class students. The implementation of the discovery learning model is carried out by dividing the three stages of learning, namely Introduction, core activities (stimulation, problem statement, data processing, verification, generalisation), and closing activities. The results showed that there was a significant difference between the initial assessment and the final assessment using the discovery learning model. Based on the data obtained, it is known that there is a difference from the initial assessment of students who still have difficulty in writing exposition texts and the final assessment of 25 students completing the exposition text completely. Judging from the increased average student results, it can be concluded that the use of the discovery learning model is successfully used in learning to write expository texts.